The Influence of Work From Home and Work-Life Balance on Employee Performance at PT Buana Bara Sejahtera - Solihin, Anip (ProBisnis : Jurnal Manajemen, 2025)
This study aims to examine the influence of Work From Home (WFH) and Work-Life Balance on employee performance at PT Buana Bara Sejahtera. As remote work becomes increasingly common, understanding its implications for individual performance and personal well-being has become essential for human resource management. This research uses a quantitative approach with data collected through questionnaires distributed to 100 employees who have experienced remote work. The results of multiple linear regression analysis show that both WFH and Work-Life Balance have a significant and positive impact on employee performance, both partially and simultaneously. These findings suggest that flexible working arrangements, when supported by a healthy balance between professional and personal life, contribute meaningfully to improved employee outcomes. The study highlights the importance of organizational support in implementing effective remote work policies and fostering a work environment that prioritizes employee well-being.